Multiple benefits of multiple mating in guppies - Evans, J. P. (The National Academy of Sciences, 2000)
The rewards of promiscuity for males are undisputed. But why should a female mate promiscuously, particularly when her partners offer no resources other than sperm and increase her chances of succumbing to predation or disease? This question has been hotly debated but at present remains largely unresolved [Jennions, M. D. & Petrie, M. (2000) Biol. Rev. 75, 21–64]. One possibility is that females exploit postcopulatory mechanisms, such as sperm competition, to increase both the quality and quantity of their offspring. In this paper, we use the Trinidadian guppy, a species with a resource-free mating system, to test the hypothesis that females gain multiple benefits from multiple mating. Our results indicate that multiply mated females secure substantive advantages: They have shorter gestation times and larger broods, and they produce offspring with better developed schooling abilities and escape responses than their singly mated counterparts.